The Effectiveness of Using Audio Visual Media on Elementary School Students’ Creative Thinking Skills (Universitas Pendidikan Indonesia (UPI), 2026)
The focus of this study was the low level of creative thinking skills among fifth-grade elementary school students and the lack of use of varied instructional media, particularly audio-visual media. This study aimed to determine the effectiveness of using audio-visual media on students' creative thinking skills in fifth-grade elementary school learning. The method used in this study was a quasi-experimental design with a nonequivalent control group design. The study used a non-probability sampling technique, specifically saturated sampling. The population consisted of 44 students, namely all fifth-grade students. Data were collected using test techniques in the form of essay questions and non-test techniques in the form of observation. The data were analyzed using an independent t-test. The results of the study showed that audio-visual media were effective in improving elementary school students' creative thinking skills because they were able to produce both audio and visual elements simultaneously.